A Novel Reply to the Knowledge Argument : Wiredu's view of Quasi-Physicalism as a positive Reply to Jackson - Ruttkamp-Bloem, Emma (University of Pretoria, 2020)
Thesis (PhD)--University of Pretoria, 2019.